DEVELOPMENT OF LEARNING MEDIA FOR ELECTRIC MOTOR INSTALLATION SUBJECT BASED ON PORTABLE TRAINER IN GRADE XII (SMK Negeri 1 Kramatwatu, Serang Regency – Banten) - Ferdinan Algifari Putra (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Abstract. This research aims to (1) determine the process of making an OMRON PLC-based Portable Trainer as a learning medium for the Electric Motor Installation subject in class XII of SMKN 1 Kramatwatu; (2) know how to use the OMRON PLC-based Portable Trainer as a learning medium for the Electric Motor Installation subject in class XII SMKN 1 Kramatwatu. This research is a type of research and development or (Research and Development) referring to the ADDIE model (Branch, 2009), namely: (1) Analyze; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. The subjects of this research included 6 experts, namely: 3 lecturers at Sultan Ageng Tirtayasa University as media experts, 3 productive teachers at SMKN 1 Kramatwatu as material experts, and 30 user responses, namely students at SMKN 1 Kramatwatu as users. The instruments used include feasibility assessment sheets by media experts, feasibility assessment sheets by material experts, feasibility assessment sheets by users. The data collection method in this research is by collecting interview data, questionnaires and tests. Data analysis techniques use media feasibility analysis, product moment validity and Rating Scale. Based on the research results obtained in research using a validation instrument with 20 questions, from the validation results the total average number per aspect was 3.37, the total average for the technical aspect was 3.45. The average for instructional aspects is 3.48 with category 1 or "Very Appropriate".